NEUROTIC ANXIETY SUFFERED BY WILLY WONKA IN ROALD DAHL’S CHARLIE AND THE CHOCOLATE FACTORY - ANANG VIKI PRATAMA HADJU (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
This study uses psychoanalysis concept, namely neurotic anxiety by the main character in Charlie and The Chocolate Factory, a novel by Roald Dahl. This study finds the character’s personality, Willy Wonka in Charlie and The Chocolate Factory’s novel becomes neurotic anxiety who influenced of the three systems of personality, there are Id, Ego, and Superego from his traumatic experienced. This happens because his life principle which it has to be followed defence mechanism to overcome the conflict he experienced. Unfortunately, he thinks that the process of the competition is the best way to reduce his anxiety for a while. This study is expected to contribute to the understanding of the human mind and significance object between literature and the psychological condition. Keywords: Id, Ego, Superego, and Neurotic Anxiety.